2014
DOI: 10.2478/s12175-013-0191-5
|View full text |Cite
|
Sign up to set email alerts
|

Existence and stability of anti-periodic solutions for impulsive fuzzy Cohen-Grossberge neural networks on time scales

Abstract: ABSTRACT. By applying the method of coincidence degree and constructing suitable Lyapunov functional, some sufficient conditions are established for the existence and global exponential stability of anti-periodic solutions for a kind of impulsive fuzzy Cohen-Grossberg neural networks on time scales. Moreover an example is given to illustrate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…These models combined fuzzy operation (fuzzy AND and fuzzy OR) with cellular neural networks. Recently scholars have found that FCNNs are useful in image processing, optimization and control [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25]. The sufficient stability criteria have become one of research topic in these models.…”
Section: Introductionmentioning
confidence: 99%
“…These models combined fuzzy operation (fuzzy AND and fuzzy OR) with cellular neural networks. Recently scholars have found that FCNNs are useful in image processing, optimization and control [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25]. The sufficient stability criteria have become one of research topic in these models.…”
Section: Introductionmentioning
confidence: 99%